Clonal expansion of mitochondrial DNA deletions is a private mechanism of aging in long‐lived animals. Issue 5 (24th July 2018) - Lakshmanan, Lakshmi Narayanan; Yee, Zhuangli; Ng, Li Fang; Gunawan, Rudiyanto; Halliwell, Barry; Gruber, Jan
Abstract: Disruption of mitochondrial metabolism and loss of mitochondrial DNA (mtDNA) integrity are widely considered as evolutionarily conserved (public) mechanisms of aging (López‐Otín et al., Cell, 153, 2013 and 1194). Human aging is associated with loss in skeletal muscle mass and function (Sarcopenia), contributing significantly to morbidity and mortality. Muscle aging is associated with loss of mtDNA integrity. In humans, clonally expanded mtDNA deletions colocalize with sites of fiber breakage and atrophy in skeletal muscle. mtDNA deletions may therefore play an important, possibly causal role in sarcopenia. The nematode  Caenorhabditis elegans  also exhibits age‐dependent decline in mitochondrial function and a form of sarcopenia. However, it is unclear if mtDNA deletions play a role in  C. elegans  aging. Here, we report identification of 266 novel mtDNA deletions in aging nematodes. Analysis of the mtDNA mutation spectrum and quantification of mutation burden indicates that (a) mtDNA deletions in nematode are extremely rare, (b) there is no significant age‐dependent increase in mtDNA deletions, and (c) there is little evidence for clonal expansion driving mtDNA deletion dynamics. Thus, mtDNA deletions are unlikely to drive the age‐dependent functional decline commonly observed in  C. elegans . Computational modeling of mtDNA dynamics in  C. elegans  indicates that the lifespan of short‐lived animals such as  C. elegans  is likely too short to allow for significant clonal expansion of mtDNA deletions. Together, these findings suggest that clonal expansion of mtDNA deletions is likely a private mechanism of aging predominantly relevant in long‐lived animals such as humans and rhesus monkey and possibly in rodents.